(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Il contributo è stato sottoposto a valutazione, ed è destinato alla pubblicazione a stampa sulla rivista Il diritto ecclesiastico. SOMMARIO: 1. Introduzione - 2. Percorsi giurisprudenziali e normativi interni in materia di unioni civili - 3. Il caso Oliari contro Italia e le sue ripercussioni sul dibattito in tema di coppie same sex - 4. Conclusioni. ABSTRACT: At a supranational level, there has been a progressive evolution of the concept of family, which would not seem rooted solely on the traditional concept that refers to heterosexual marriage, nor necessarily requiring the difference in sex of the engaged couple. In Italy, the difficulties encountered in terms of legislative action at a national level, in the purpose of the definition of a legal status to the unions between persons of the same sex, have led, in recent years, many couples to turn to the European Court of Human Rights in order to obtain the recognition, within the italian legal system, of the right to marry for homosexual unions, and the right to the transcript of the marriage or registered partnership concluded abroad. This has generated a lively and stimulating legal and jurisprudential debate. The article aims to reconstruct conceptually the problem raised by the question of "egalitarian marriage", accessible to all couples, regardless of possible gender identity of the contractors, and the resulting answers and solutions offered, in a internal and supranational level, by political and judicial bodies.